Forging subregional links in transportation and logistics in South Asia - Subramanian, Uma (World Bank, 2001)
"In the wake of recent liberalization, South Asian countries are seeking to expand trade and investment links with regional and global partners. However, inadequate infrastructure combined with policy and regulatory constraints imposes significant limitations in opening up one of the poorest regions in the world.".